2006
DOI: 10.1111/j.1749-4486.2006.01139.x
|View full text |Cite
|
Sign up to set email alerts
|

How we do it: Septoplasties under local anaesthetic are suitable for short stay surgery; the clinical outcomes

Abstract: . Septoplasties can be performed under local anaesthesia. However, careful prevention and treatment of pain during the operation is essential. . Septoplasties are suitable operations for short-stay surgery. .Two-years post-operative, septoplasty relieved the symptoms well or excellently in 55% and moderately in 27% of the cases. . Specialists prescribe more prophylactic antibiotics than residents (47%versus 29%P = 0.02). .Post-operative antibiotics do not appear to prevent the development of post-operative inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 9 publications
1
31
0
1
Order By: Relevance
“…76 % answered yes and 24 % answered no. This corresponds with other studies [6]. We did sub analyses and found that 86 % of the patients who underwent surgery for the first time were satisfied but only 54 % of the patients who had undergone previous nasal septoplasty were satisfied.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…76 % answered yes and 24 % answered no. This corresponds with other studies [6]. We did sub analyses and found that 86 % of the patients who underwent surgery for the first time were satisfied but only 54 % of the patients who had undergone previous nasal septoplasty were satisfied.…”
Section: Discussionmentioning
confidence: 74%
“…Nevertheless, the gain of this surgery has been questioned. Some studies have showed moderate to excellent results [6,7] but a new study from Sweden suggests that the results are unsatisfactory [8]. Additionally, radiofrequency therapy of the inferior turbinate is done frequently as an attempt to reduce nasal congestion or hypertrophy of the inferior turbinate [9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cosmetic plastic head and neck surgeries showed a clear trend toward the increasing use of local anaesthetics [10] . Septoplasties are well documented example of suitable operations for short-stay surgery under local anaesthesia [11,12] . In addition there are emerging new methods such as voice prosthesis insertion [13] and tracheooesophageal puncture [14] that require no general anaesthesia but can also be performed in local anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine can control the degree of sedation according to the dosage while minimizing respiratory inhibition, and also has an analgesic effect by suppressing the sympathetic nerve system; therefore, it has recently been used as anesthesia or an anesthesia supplement in various procedures [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%